Platinum-Based Neoadjuvant Chemotherapy Before Radical Prostatectomy for Locally Advanced Prostate Cancer With Homologous Recombination Deficiency: A Case Report - Zhuang, Junlong; Zhang, Shun; Qiu, Xuefeng; Fu, Yao; Ai, Shuyue; Zhao, Tingting; Yang, Yining; Guo, Hongqian (Frontiers in Oncology, 2022)
More emerging evidence showed that homologous recombination (HR) defect (HRD) may predict sensitivity to platinum agents in metastatic prostate cancer (PCa). Platinum-based neoadjuvant chemotherapy for PCa with HRD has not been reported. Here, we reported a man diagnosed as locally advanced PCa with high Gleason Score (5 + 5) and low PSA level (5.2 ng/ml). Next-generation sequencing (NGS) demonstrated HRD. He received six cycles of platinum-based neoadjuvant chemotherapy before radical prostatectomy (RP). Fifteen months after RP, his PSA level was still undetectable, and no imaging progression was found, indicating a potential role for platinum-based neoadjuvant chemotherapy in locally advanced PCa with HRD.